2021
DOI: 10.1126/sciadv.abd5363
|View full text |Cite
|
Sign up to set email alerts
|

How usefulness shapes neural representations during goal-directed behavior

Abstract: Value is often associated with reward, emphasizing its hedonic aspects. However, when circumstances change, value must also change (a compass outvalues gold, if you are lost). How are value representations in the brain reshaped under different behavioral goals? To answer this question, we devised a new task that decouples usefulness from its hedonic attributes, allowing us to study flexible goal-dependent mapping. Here, we show that, unlike sensory cortices, regions in the prefrontal cortex (PFC)—usually assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
27
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 60 publications
(130 reference statements)
9
27
0
Order By: Relevance
“…Our results are consistent with choice theories that propose that preferences are not stored in an immutable format, but rather constructed at the time of choice and can be influenced by cognitive and contextual factors (26,(36)(37)(38). Cognitive reappraisal, or the modification of the way one thinks about a stimulus in order to change its emotional or other subjective evaluations (33,(39)(40)(41), is a form of goaldependent evaluation of previous and current experiences.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our results are consistent with choice theories that propose that preferences are not stored in an immutable format, but rather constructed at the time of choice and can be influenced by cognitive and contextual factors (26,(36)(37)(38). Cognitive reappraisal, or the modification of the way one thinks about a stimulus in order to change its emotional or other subjective evaluations (33,(39)(40)(41), is a form of goaldependent evaluation of previous and current experiences.…”
Section: Discussionsupporting
confidence: 89%
“…The participants in this study were self-reported dieters who evaluated the same fifty food items in the context of three separate goals while undergoing functional magnetic resonance imaging (Figure 1). To examine the multi-faceted goal directed representational patterns of episodic memory traces we used representational similarity analyses (RSA), a technique well suited to capture such patterns (24)(25)(26)20).…”
Section: Resultsmentioning
confidence: 99%
“…A good candidate could be the mPFC or the vmPFC in humans ( Mack et al, 2020 ; Tse et al, 2011 ). Indeed, the vmPFC exhibits value signals directly modulated by cognitive requirements ( Castegnetti et al, 2021 ). Our results expose a potential mechanism of how the vmPFC interacts with the HPC in construction of goal-relevant abstractions.…”
Section: Discussionmentioning
confidence: 99%
“…2 C). Recent work has extended these findings to show that even arbitrary goals such as lighting a fire versus tying a boat can flexibly warp putative value representations of options to reflect their usefulness for that goal (Castegnetti, Zurita, & De Martino, 2021), and that multiple potentially conflicting goals can be simultaneously represented in mOFC (Moneta et al, 2021). participants respond faster when choosing among higher value options (overall value effect) regardless of whether their task is to choose the best or the worst option.…”
Section: The Influence Of Goals On How We Represent Valuementioning
confidence: 92%